Synchrotron-based high-pressure research in materials science. (8th June 2016) - Chen, Bin; Lin, Jung-Fu; Chen, Jiuhua; Zhang, Hengzhong; Zeng, Qiaoshi
Abstract: Abstract : The integration of synchrotron and high-pressure techniques has significantly advanced research in materials science, giving rise to many important discoveries in physics, chemistry, environmental science, and many other fields of physical and engineering sciences. The relevant frontier work in multiple disciplines is reviewed. The selected studies include high-pressure superconductivity, lattice dynamics of materials, plastic deformation of nanomaterials, polyamorphic transitions and devitrification in metallic glass, rheology of minerals, and high-pressure chemistry probing.